Distributions of Noble Metals (Ag, Au) in the Lower Horizons of the Gizilbulag Copper-Cement Deposit - Huseynov, G.S.; Karimli, T.E. (Herald of Azerbaijan Engineering Academy, 2025)
The distribution of gold and silver in various types of ores and monomineral fractions of main sulfide (pyrite, chalcopyrite, sphalerite) minerals is considered. It is established that in various types of ores and monomineral fractions of sulfide minerals, the distribution of noble minerals (Ag, Au) is distributed unevenly. So high gold contents are observed in the quartz-chalcopyrite association, where the average content is 9.2g/t. This is probably due to the fact that the main ore mineral containing gold in the deposit is chalcopyrite, as evidenced by the gold content of monomineral fractions of chalcopyrite, averaging 6.2g/t. High average silver is typical for chalcopyrite-sphalerite types of ores (8.6g/t). Based on the results of the analyses, histograms of the distribution of gold and silver contents in various types of ores and monomineral fractions were constructed. The distribution of gold and silver in lower horizons of the deposit. It has been established that in the 755 m horizon there is a high gold content (20-40g/t), and in the central part of the horizon the silver content is 40-60g/t. At the 725 m horizon the gold content is 30g/t and an increased concentration of silver (20-30g/t) is also noted in the central part of the horizon. The minimum Au:Ag (1:1) ratio is observed in the central part of the 755 m horizon, and at the 725 m horizon the gold-silver ratio is 1:0.8.